2019
DOI: 10.1111/obr.12955
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of body mass gain after deep brain stimulation of the subthalamic nucleus in patients with Parkinson's disease

Abstract: This systematic review investigated the effects of deep brain stimulation of the subthalamic nucleus on extent and time course of body mass changes in patients with Parkinson's disease. A computerized search identified relevant articles using a priori defined inclusion and exclusion criteria. A descriptive analysis was calculated for the main outcome parameters body mass and BMI. Thirty-eight out of 206 studies fulfilled the inclusion criteria (979 patients aged 59.0±7.5 years). Considering the longest follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 71 publications
1
25
0
3
Order By: Relevance
“…Interestingly, many researchers have reported that weight gain (WG) is common in patients with PD after DBS of the subthalamic nucleus (STN-DBS) (9). This is concerning because WG may lead to additional health complications such as obesity and diabetes (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, many researchers have reported that weight gain (WG) is common in patients with PD after DBS of the subthalamic nucleus (STN-DBS) (9). This is concerning because WG may lead to additional health complications such as obesity and diabetes (6).…”
Section: Introductionmentioning
confidence: 99%
“…This is concerning because WG may lead to additional health complications such as obesity and diabetes (6). Some potential mechanisms underlying WG in patients with PD after STN-DBS treatment have been suggested, including the improvement of resting tremor and dyskinesias, reduction in energy expenditure (EE), changes in eating behavior and food intake, perturbations of homeostatic control, changes in hormone and neurotransmitter systems, and improvement in motor function; however, the exact mechanism underlying WG remains unknown (9).…”
Section: Introductionmentioning
confidence: 99%
“…Different treatment strategies in PD have diverse impacts on body weight. For example, deep brain stimulation (DBS), an effective treatment option for motor complications, has been associated with weight gain among treated PD patients [ 17 ]. Similar results have also been observed during the initiation of dopamine replacement therapy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review (n = 979), it was noted that body weight increased across the studies to a mean value of 5.71 kg and was higher with longer duration of follow-ups. 12 The literature is sparse in relation to pharmacological interventions including LCIG and apomorphine pumps. Fabbri et al (2019), in their analysis, noted 30/44 patients of PD who were on LCIG, noted an average weight loss of 9.9% ± 10.5% (7.6 ± 7.1 kg) over a period of 51.6 ± 28.5 months of therapy.…”
mentioning
confidence: 99%